Corrosion-resistant modified polyurethane coating as well as preparation method and application thereof
By introducing cellulose nanocrystals extracted from the eutectic solvent method into the polyurethane coating, the shortcomings of modified polyurethane coatings in high strength and high durability applications are solved, and efficient and environmentally friendly corrosion resistance and mechanical properties are improved.
Patent Information
- Application Number
- CN202510011412.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing modified polyurethane coatings are limited in application in high strength and high durability applications, complex operating processes, and most of the modifiers are chemical synthetic materials, which are prone to environmental pollution and high production costs, making it difficult to meet the requirements of sustainable development.
The polyurethane matrix was modified by cellulose nanocrystals (CNC), and plant lignocellulose nanocrystals were extracted by eutectic solvent method, and more ether bonds and C-H structures were introduced into the structure of the polyurethane to optimize the mechanical properties and corrosion resistance of the material.
It significantly improves the corrosion resistance and mechanical properties of polyurethane coatings, reduces production costs, and realizes a low-carbon and environmentally friendly preparation process, which is suitable for protection needs in a variety of complex environments.
Smart Images

Figure HDA0005228449450000011 
Figure HDA0005228449450000012 
Figure HDA0005228449450000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a corrosion-resistant modified polyurethane coating and a preparation method and application thereof. Background Art
[0002] With the continuous expansion of the scale of marine engineering and the increasing complexity of the operating environment, marine engineering equipment faces severe corrosion challenges. The salt, oxygen and extreme meteorological conditions in seawater pose a long-term corrosion threat to metal equipment, threatening the safety, reliability and life of the equipment. Therefore, the use of effective corrosion protection measures has become a vital task. In order to extend the service life of marine equipment and reduce maintenance costs, it is crucial to develop efficient anti-corrosion coating materials, which provide a reliable protective barrier for marine engineering equipment.
[0003] As a functional coating, polyurethane (PU) coating has been widely used in various fields such as construction engineering, transportation, military defense, etc. due to its advantages such as good corrosion resistance, low-temperature flexibility and wear resistance. In terms of corrosion protection, the use of PU coating for corrosion protection of engineering structures is an economical and safe method. In recent years, researchers at home and abroad have developed various methods to modify PU coatings to enhance their anti-corrosion properties. For example, Liu Jiaqi et al. modified PU coatings using amino silicone oil synthesized from dichloromethylsilane and allylamine (Research on the Anti-corrosion Performance of Modified Polyurethane Resin Coatings [J]. Coatings and Protection, 2019, 40(12): 38-42.). Jin et al. modified WPU with isophorone diisocyanate, polypropylene glycol, 2,2-dihydroxymethyl propionic acid and two types of epoxy resins (E-20 and E-44) as the main raw materials (Study on synthesis and properties of waterborne polyurethane modified by epoxy resin [J]. Applied Mechanics and Materials, 2013, 395-396: 423-426). Invention patent CN114058261A discloses a heat-resistant and acid-resistant anticorrosive coating for brick desulfurization chimneys and its preparation method, synthesizing unmodified polyurethane, synthesizing organosilicon oligomers using silane coupling agents, and using them to chemically modify polyurethane. Invention patent CN112759999A discloses a method for preparing a silicone-modified water-based acrylic polyurethane anticorrosive coating, wherein polyols such as polytetrahydrofuran ether polyol, polybutylene adipate-1,4-diol, polyhexylene adipate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and other diisocyanates are selected, and silicone intermediates and acrylic monomers are introduced to copolymerize and modify water-based polyurethane. Although the above research has improved the anticorrosive properties of polyurethane to a certain extent, for example, by introducing silicone oligomers, epoxy resins or water-based acrylic modifiers to improve the heat resistance and acid resistance of the coating, there are still some limitations. First, these methods are insufficient in optimizing the mechanical properties of polyurethane, resulting in limited applicability in high-strength and high-durability applications. Secondly, the operating process is relatively complicated, and the modifiers used are mostly chemical synthetic materials, which are prone to environmental pollution during the preparation process and are difficult to meet the requirements of sustainable development. In addition, the addition amount of the modifier is relatively high, which directly pushes up the production cost and reduces the economy of industrial application. Therefore, it is necessary to develop a coating that can maintain excellent anti-corrosion performance while improving mechanical properties, and to achieve a low-cost, low-carbon and environmentally friendly preparation process to meet the needs of modern industry for high-performance anti-corrosion materials. Summary of the invention
[0004] In view of the above-mentioned problems existing in the prior art, the present invention provides a corrosion-resistant modified polyurethane coating and a preparation method and application thereof. While ensuring excellent anti-corrosion performance, the coating also has the advantages of high strength, low cost and environmental protection. It can be widely used in protection needs in various complex environments, overcomes the limitations of traditional modified polyurethane coatings in practical applications, and solves the problems of existing modified polyurethane coatings such as poor mechanical properties, large amount of modifier added, high cost and non-compliance with sustainable development requirements.
[0005] To achieve the above object, the present invention adopts the following scheme: a method for preparing a corrosion-resistant modified polyurethane coating, comprising the following steps:
[0006] 1) dissolving polytetrahydrofuran in a solvent and adding a catalyst, stirring evenly to obtain a solution A; dissolving a diisocyanate compound in a solvent to obtain a solution B;
[0007] 2) Under a nitrogen atmosphere, the solution A and the solution B obtained in step 1) are mixed evenly, and then reacted at 60° C. to 80° C. for 2 h to 8 h to obtain a prepolymer;
[0008] 3) cooling the prepolymer obtained in step 2) to room temperature and then transferring it to an environment of -20°C to 10°C and continuing stirring, and then slowly dropping a chain extender into the prepolymer to obtain a reaction solution; the reaction solution also includes cellulose nanocrystals, which are added to solution A, solution B, a mixed solution or a reaction solution, and the cellulose nanocrystals are extracted by a low eutectic solvent method;
[0009] 4) The reaction solution obtained in step 3) is heated to 60° C. to 80° C. and the reaction is continued for 6 h to 24 h. After the reaction is completed, the heating is stopped and the solution is transferred to a mold and vacuum dried to a constant weight to obtain the corrosion-resistant modified polyurethane coating.
[0010] Preferably, the cellulose nanocrystals are derived from plant wood fibers, preferably but not limited to peanut shells, ramie and / or waste paper fibers.
[0011] Preferably, the deep eutectic solvent method specifically comprises the following steps:
[0012] S1: heating and stirring choline chloride and guaiacol, then adding AlCl3·6H2O, and continuing heating and stirring until a uniform transparent liquid is formed to obtain a deep eutectic solvent;
[0013] S2: Place plant lignocellulose and a low eutectic solvent in a reduced pressure glass bottle, shake them evenly, place them in an oil bath at 100°C to 140°C for 2h to 4h, add deionized water to quench the reaction, and then put them into a dialysis bag with a molecular weight of 8000 to 14000 and dialyze them in deionized water until the pH of the solution becomes neutral;
[0014] S3: placing the solution obtained in step S2 in an ice bath for ultrasonic treatment until the solution becomes transparent. After the ultrasonic treatment, collecting the supernatant by centrifugation and freeze-drying to obtain the cellulose nanocrystals.
[0015] Preferably, in step S1, the molar ratio of choline chloride, guaiacol and AlCl3·6H2O is 1:1:(0.01-0.1); the heating temperature is 70-90°C, and the stirring speed is 500-1000 rpm.
[0016] Preferably, the solid-liquid ratio of the plant lignocellulose to the low eutectic solvent is (0.5-1) g:40 g; during the ultrasonic treatment, the ultrasonic output power is 600-1000 W, the on / off time is (1-4 s) / (1-4 s), and the ultrasonic time is 5-15 min.
[0017] Preferably, the diisocyanate compound is one or more of isophorone diisocyanate, 1,6-hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate and dicyclohexylmethane diisocyanate; and the solvent is N,N'-dimethylacetamide, N,N'-dimethylformamide, toluene or acetone.
[0018] Preferably, the mass ratio of the prepolymer to the cellulose nanocrystals in the reaction solution is 100:(0.1-1).
[0019] Preferably, the chain extender is isophorone diamine, dicyclohexylmethane, ethylenediamine, diaminodiphenylmethane or triethanolamine; and the catalyst is dibutyltin diacid, dibutyltin diacetate or titanate.
[0020] Another object of the present invention is to provide a corrosion-resistant modified polyurethane coating prepared by the above method.
[0021] Another object of the present invention is to provide the modified polyurethane coating for use in corrosive environments to protect metal substrates from corrosion, including but not limited to acidic corrosive environments (such as acid rain or acidic industrial waste gas), alkaline corrosive environments (such as alkali-containing waste liquids or alkaline cleaning agents), saline corrosive environments (such as marine salt spray or snow-melting salts), and aqueous corrosive environments (such as high humidity or underwater immersion conditions). The coating significantly enhances the adhesion and barrier properties to the metal surface by optimizing the formula and introducing modified components, effectively preventing the penetration of corrosive media and extending the service life of the metal structure.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention introduces cellulose nanocrystals (CNC) to modify the polyurethane matrix, and for the first time discovers that the source of CNC plant wood fiber and its extraction method by a low eutectic solvent method can effectively improve the corrosion resistance and mechanical properties of the material. On the one hand, CNC has a nanoscale size and a high specific surface area, and can be evenly dispersed in the polyurethane matrix to form a dense protective layer, effectively blocking the penetration of corrosive media. On the other hand, during the compounding process of the raw materials, CNC introduces more ether bonds and CH structures into the structure of the polyurethane, which is attributed to the signal changes caused by the physical embedding and interface interaction of CNC, thereby changing the microstructure and performance characteristics of the material, which can significantly affect the mechanical, thermal or interface properties of the material, thereby improving the electrochemical stability and corrosion resistance of the polyurethane. In addition, the addition of CNC optimizes the interface structure of polyurethane, forms a uniform and stable nano-interface distribution, improves the storage modulus (G') and loss modulus (G"), and exhibits stronger impact resistance and durability. Compared with traditional materials such as polyaniline and epoxy resin, the impedance value of the modified polyurethane of the present invention in a simulated marine environment is significantly improved, showing a more excellent corrosion resistance, overcoming the deficiencies of traditional anti-corrosion materials in mechanical properties, corrosion resistance and environmental protection, and showing excellent comprehensive performance, providing an efficient and green solution for anti-corrosion applications in marine environments, and is expected to provide new research methods and approaches for the preparation of new corrosion-resistant coatings, and provide innovative ideas for the development of a new generation of anti-corrosion coating materials.
[0024] 2. The present invention uses renewable biomass such as ramie, peanut shells, and waste paper fibers as raw materials, all of which come from natural biological materials, achieving the goal of "turning waste into treasure", with low price and good biocompatibility. It adopts green and environmentally friendly DES solvent extraction technology, avoids the pollution of the environment during the preparation of chemical materials such as polyaniline, and meets the requirements of sustainable development. In addition, the amount of CNC used in the present invention only needs to be added at 0.1%, which can significantly improve the material properties, which is far lower than the demand for high-proportion fillers in traditional anti-corrosion coatings, reducing production costs. The modified polyurethane of the present invention not only improves the corrosion resistance of the material, but also performs well in mechanical strength. It can effectively protect the metal substrate under corrosive environments and has good application scenarios in marine anti-corrosion coatings, ship coatings, and protection of marine equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a flow chart of the preparation of cellulose nanocrystals of the present invention.
[0026] Figure 2 This is the infrared spectrum analysis diagram of peanut shell / ramie / waste paper fiber before and after DES solvent pretreatment.
[0027] Figure 3 This is the infrared spectrum analysis diagram of modified polyurethane coating.
[0028] Figure 4 DMA tests of different modified polyurethane coatings; A is the storage modulus-frequency relationship diagram, B is the loss modulus-frequency relationship diagram, and C is the loss factor-frequency relationship diagram.
[0029] Figure 5 Electrochemical impedance spectroscopy of different modified polyurethane coatings. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific examples, but the examples cited are not intended to limit the present invention. Experimental methods without specific conditions in the preferred embodiments are usually carried out under conventional conditions or under conditions recommended by reagent manufacturers.
[0031] 1. A method for preparing a corrosion-resistant modified polyurethane coating.
[0032] Example 1
[0033] (1) Preparation of cellulose nanocrystals, the flow chart is as follows Figure 1 As shown, the specific steps include:
[0034] 1) Choline chloride (ChCl) and guaiacol (GG) are placed in a beaker, and then AlCl3·6H2O is added to make the molar ratio of ChCl, GG and AlCl3·6H2O be 1:1:0.07, and then it is placed on a constant temperature magnetic stirrer at 90°C and a speed of 500 rpm for heating and stirring until a uniform transparent liquid is formed to obtain a deep eutectic solvent (DES).
[0035] 2) Peanut shells and a low eutectic solvent are placed in a reduced pressure glass bottle at a solid-liquid ratio of 1:40 (w / w), shaken evenly, and reacted in a 120°C oil bath for 3 hours. After the pretreatment, deionized water is added to quench the reaction, and then it is loaded into a dialysis bag with a molecular weight of 8000 to 14000 and dialyzed in deionized water until the pH of the solution becomes neutral.
[0036] 3) placing the obtained solution in an ice bath for ultrasonic treatment to maintain the temperature below 40°C, with an ultrasonic output power of 600 W, an on / off time of 2 / 2 s, and an ultrasonic time of 15 min. After the ultrasonic treatment, the solution was separated at 4000 rpm for 5 min using a centrifuge, and the turbid supernatant was collected and the ultrasonic treatment was repeated until the supernatant in the centrifuge tube became transparent. The supernatant was collected by centrifugation and freeze-dried to obtain the cellulose nanocrystals.
[0037] (2) Preparation of corrosion-resistant modified polyurethane coatings
[0038] 1) The polytetrahydrofuran (PTMEG) was dried at 110°C for 4 hours to remove moisture, 14 g of PTMEG was put into a 100 ml three-necked flask, and then N, N'-dimethylacetamide (DMAc) was added as a solvent, and 0.01 g of catalyst dibutyltin diacid DBTDL was added dropwise, and stirred at a speed of 2000 rpm to obtain solution A; isophorone diisocyanate (IPDI) (3.46 g) and 1,6-hexamethylene diisocyanate (HDI) (2.60 g) were added to the solvent N, N'-dimethylacetamide (DMAc), and stirred at a speed of 2000 rpm to obtain solution B; the total amount of the solvent in solution A and the solvent in solution B was 45 ml.
[0039] 2) Under a nitrogen atmosphere, the obtained solution A and solution B were mixed evenly, and then placed at 80° C. for reaction for 4 hours to obtain a mixed solution.
[0040] 3) The obtained mixed solution was first cooled to room temperature and then transferred to a 0°C environment and continued to stir for 10 minutes, and then isophorone diamine IPDA (3.80 g) was slowly added dropwise within 30 minutes to obtain a reaction solution. At the same time, 2 mg of cellulose nanocrystals pre-dispersed in a DMAC solvent were added to the reaction solution, and then heated to 60°C and maintained at this temperature for 12 hours. After the reaction was completed, the heating was stopped, and the mixture was transferred to a mold and vacuum dried to constant weight to obtain the corrosion-resistant modified polyurethane coating.
[0041] Example 2
[0042] The plant wood fiber is ramie, and the other steps are the same as those in Example 1.
[0043] Example 3
[0044] The plant wood fiber is waste paper fiber, and the other steps are the same as those in Example 1.
[0045] Example 4
[0046] The cellulose nanocrystals were directly added into solution A, and the other steps were the same as those in Example 3.
[0047] Example 5
[0048] The cellulose nanocrystals were directly added to solution B, and the other steps were the same as those in Example 3.
[0049] Example 6
[0050] The cellulose nanocrystals are directly added to the prepolymer, and the other steps are the same as those in Example 3.
[0051] Comparative Example 1
[0052] Microcrystalline cellulose replaces peanut shells, and the cellulose nanocrystals are extracted by sulfuric acid method. The other steps are the same as those in Example 1.
[0053] Comparative Example 2
[0054] Microcrystalline cellulose replaced peanut shells, and other steps were the same as in Example 1.
[0055] 2. Performance Testing
[0056] 1. The samples of peanut shell / ramie / waste paper fiber and low eutectic solvent pretreatment in the present invention were washed with 100 mL of ethanol solution (ethanol and water were mixed at a ratio of 1:2 (v / v)) and soaked and stirred overnight. The soaked samples were vacuum filtered and washed with ethanol solution until the filtrate was clear and colorless. The solid fraction was dried at 60°C and placed in a dryer. Then, the samples were analyzed by infrared spectroscopy using a Fourier transform infrared spectrometer. The results are as follows: Figure 2 shown.
[0057] from Figure 2 It can be seen that the chemical structures of different biomasses have undergone certain changes before and after treatment with the low eutectic solvent. At 3340 cm-1, it is the OH stretching vibration. After treatment with the low eutectic solvent of the present invention, the OH stretching vibration peak weakened, indicating that the low eutectic solvent treatment reduced the free hydroxyl groups in the sample. This may be due to the partial degradation of hemicellulose and lignin, and the released hydroxyl groups are blocked by hydrogen bonds in the low eutectic solvent. At 3010-2780 cm-1, it is the CH stretching vibration. After treatment with the low eutectic solvent, the CH stretching vibration peak intensity is slightly enhanced, especially for ramie and peanut shell samples. This may be related to the partial dissolution of lignin and the relative increase in the proportion of cellulose. At 1698-1555 cm-1, it is the C=O stretching vibration. After treatment with the low eutectic solvent, the C=O stretching vibration peak is significantly enhanced, especially for the waste paper sample. This may be due to the degradation of lignin during the treatment with the low eutectic solvent, generating carbonyl or carboxylic acid compounds. At 1246cm-1 and 1035cm-1, the COC stretching vibration peak intensity is slightly reduced after treatment, indicating that the COC bonds of some hemicelluloses are broken or dissolved. At 897cm-1, the CH peak intensity is significantly reduced after treatment, especially for ramie and waste paper samples, indicating that lignin is partially degraded and the CH group is reduced. Therefore, the low eutectic solvent of the present invention can remove a large amount of lignin and hemicellulose from biomass while retaining the basic skeleton structure of cellulose, which is a gentle and efficient treatment method.
[0058] 2. The modified polyurethane coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were analyzed by infrared spectroscopy using a Fourier transform infrared spectrometer, and polyurethane (PU) was used as a control. The results are as follows: Figure 3 shown.
[0059] from Figure 3 It can be seen that there are differences in the absorption peaks of different CNC modified polyurethanes, reflecting that the source and treatment method of CNC have a great influence on the material structure. Specifically: 3340cm-1 is the OH absorption peak, and the OH stretching vibration absorption peak of all modified samples is slightly enhanced compared with pure PU, indicating that the addition of CNC provides more hydroxyl groups and enhances the hydrogen bonding effect. 3010~2780cm-1 is the CH absorption peak, and all modified samples have characteristic absorption peaks within this range, indicating that the addition of CNC has little effect on the CH bond structure. 1771~1555cm-1 is the C=O absorption peak, and the C=O absorption peak of the modified sample is enhanced compared with pure PU; 1246-1 and 1053cm-1 are COC absorption peaks and CH absorption peaks, respectively. Compared with PU and Comparative Example 1, Examples 1 to 3 and Comparative Example 2 have stronger absorption peaks in these areas, indicating that CNC extracted by the low eutectic solvent method introduces more ether bonds and CH structures into the structure.
[0060] 3. The modified polyurethane coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to DMA testing using a dynamic thermal mechanical analyzer. Specifically: the modified polyurethane samples were cut into 30×7×0.2mm, and a frequency scan was performed at 0°C. The strain was fixed at 1%, and the frequency range was 10Hz-0.1Hz. Polyurethane (PU) was used as a control. The storage modulus, also known as the elastic modulus, refers to the amount of energy stored in the material due to the reversible elastic deformation when the material is deformed, reflecting the elasticity of the material. The loss modulus, also known as the viscous modulus, refers to the amount of energy lost due to the irreversible viscous deformation when the material is deformed, reflecting the viscosity of the material. The ratio of the loss and storage moduli is called the loss factor, which reflects the viscosity-elasticity ratio of the material. The results are as follows: Figure 4 shown.
[0061] The storage modulus (G'), loss modulus (G") and loss factor of different modified polyurethane coatings vary with frequency as shown in Figure 2. Figure 4 A. Figure 4 B and Figure 4 As shown in Figure C, it can be found that in the entire scanning frequency range, the storage modulus of Examples 1 to 3 is higher than that of Comparative Examples 1 to 2, and the loss modulus of Examples 1 to 3 is higher than that of Comparative Examples 1 to 2, which indicates that the introduction of CNC derived from plant wood fibers has a significant enhancement effect on the dynamic mechanical properties of polyurethane coatings. The dual improvement of storage modulus and loss modulus indicates that the material has been balanced and optimized in terms of elasticity and viscous behavior. The storage modulus and loss modulus performance of Comparative Example 1 and Comparative Example 2 are similar, but Comparative Example 2 is better, indicating that the CNC extracted by the DES method has better performance in modified polyurethane. In addition, the loss factor (Tanδ) of Examples 1 to 3 is less than that of Comparative Examples 1 to 2, which indicates that the elastic properties of the modified polyurethane coating are dominant and show higher deformation recovery efficiency. The results show that the type of raw materials and the extraction method significantly affect the modification effect of CNC. The present invention significantly improves the resistance of the modified polyurethane coating to external permanent deformation, and also makes the modified polyurethane coating have better viscoelasticity and stiffness, thereby improving its overall mechanical properties.
[0062] 4. The modified polyurethane coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to electrochemical impedance spectroscopy (EIS) analysis, and the electrochemical impedance spectroscopy (EIS) results of the modified polyurethane coatings were obtained in 3.5% NaCl simulated seawater using an electrochemical workstation. In the three-electrode system, the contact area between all samples (working electrodes) and the corrosive electrolyte was 1 cm 2 . Under an AC voltage of 100Mv rms, the measurement frequency is from 10 4 Hz to 10 -2Hz. Polyurethane (PU) was used as a control. The electrochemical impedance curves of the modified polyurethane coatings are composed of a semicircle in the high-frequency region and a slant line in the low-frequency region. Figure 5 shown.
[0063] from Figure 5 It can be seen from the electrochemical impedance spectrum that the CNC extracted by the DES method significantly improves the corrosion resistance of polyurethane. The modified polyurethane coatings prepared in Examples 1 to 3 show higher impedance values in the low-frequency region (<10Hz), indicating that they have better shielding effect on corrosive media. Compared with the comparative example and PU, the impedance modulus of the coating of the present invention is increased by nearly 4 orders of magnitude. At the same time, in the high-frequency region, the modified polyurethane coatings prepared in Examples 1 to 3 also have higher impedance values compared with the comparative example and PU, indicating that they have good electrochemical stability. It can be seen that the present invention significantly improves the corrosion resistance of polyurethane. It shows that the plant wood fiber source of CNC and its low eutectic solvent extraction method work together to improve the electrochemical stability and corrosion resistance of polyurethane. This may be due to the nanoscale size, high specific surface area and good dispersibility of CNC derived from plant wood fibers, as well as the mild conditions and surface modification effects of the DES extraction method, which jointly promote the dispersion and interface interaction of CNC in the polyurethane matrix. This synergistic effect improves the density and shielding properties of the polyurethane coating, thereby significantly improving its electrochemical stability and corrosion resistance.
[0064] It should be noted that the properties of the modified polyurethane coatings obtained in Examples 4 to 6 are similar to those in Example 3 and are not listed here one by one.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the applicant has described the present invention in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that modifications or equivalent substitutions of the technical solution of the present invention without departing from the purpose and scope of the technical solution of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a corrosion-resistant modified polyurethane coating, characterized in that: The following steps are involved: 1) dissolving polytetrahydrofuran in a solvent and adding a catalyst, stirring evenly to obtain a solution A; dissolving a diisocyanate compound in a solvent to obtain a solution B; 2) Under a nitrogen atmosphere, the solution A and the solution B obtained in step 1) are mixed evenly, and then placed at 60° C. to 80° C. for reaction for 2 to 8 hours to obtain a prepolymer; 3) cooling the prepolymer obtained in step 2) to room temperature and then transferring it to an environment of -20°C to 10°C and continuing to stir it, then slowly dropping a chain extender into the prepolymer to obtain a reaction solution; the reaction solution also includes cellulose nanocrystals, which are added to solution A, solution B, the prepolymer or the reaction solution, and the cellulose nanocrystals are extracted by a low eutectic solvent method; 4) The reaction solution obtained in step 3) is heated to 60° C. to 80° C. and the reaction is continued for 6 h to 24 h. After the reaction is completed, the heating is stopped and the solution is transferred to a mold and vacuum dried to a constant weight to obtain the corrosion-resistant modified polyurethane coating.
2. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 1, characterized in that: The cellulose nanocrystals are derived from plant wood fibers, preferably peanut shells, ramie and / or waste paper fibers.
3. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 1, characterized in that: The deep eutectic solvent method specifically comprises the following steps: S1: heating and stirring choline chloride and guaiacol, then adding AlCl3·6H2O, and continuing heating and stirring until a uniform transparent liquid is formed to obtain a low eutectic solvent; S2: Place plant lignocellulose and a low eutectic solvent in a reduced pressure glass bottle, shake them evenly, place them in an oil bath at 100°C to 140°C for 2 to 4 hours, add deionized water to quench the reaction, and then put them into a dialysis bag with a molecular weight of 8000 to 14000 and dialyze them in deionized water until the pH of the solution becomes neutral; S3: placing the solution obtained in step S2 in an ice bath for ultrasonic treatment until the solution becomes transparent. After the ultrasonic treatment, collecting the supernatant by centrifugation and freeze-drying to obtain the cellulose nanocrystals.
4. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 3, characterized in that: In the step S1, the molar ratio of choline chloride, guaiacol and AlCl3·6H2O is 1:1:(0.01-0.1); the heating temperature is 70-90° C., and the stirring speed is 500-1000 rpm.
5. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 3, characterized in that: The solid-liquid ratio of the plant lignocellulose to the low eutectic solvent is (0.5-1) g:40 g; during the ultrasonic treatment, the ultrasonic output power is 600-1000 W, the on / off time is (1-4 s) / (1-4 s), and the ultrasonic time is 5-15 min.
6. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 1, characterized in that: The diisocyanate compound is one or more of isophorone diisocyanate, 1,6-hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate and dicyclohexylmethane diisocyanate; the solvent is N,N'-dimethylacetamide, N,N'-dimethylformamide, toluene or acetone.
7. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 1, characterized in that: The mass ratio of the prepolymer to the cellulose nanocrystals in the reaction solution is 100:(0.1-1).
8. The method for preparing the corrosion-resistant modified polyurethane coating according to claim 1, characterized in that: The chain extender is isophorone diamine, dicyclohexylmethane, ethylenediamine, diaminodiphenylmethane or triethanolamine; the catalyst is dibutyltin diacid, dibutyltin diacetate or titanate.
9. A corrosion-resistant modified polyurethane coating prepared according to the method according to any one of claims 1 to 8.
10. The modified polyurethane coating as claimed in claim 9 is used in a corrosive environment to provide efficient anti-corrosion protection for a metal substrate, wherein the corrosive environment is an acidic corrosive environment, an alkaline corrosive environment, a saline corrosive environment or an aqueous corrosive environment.
Citation Information
Patent Citations
Preparation method of organic silicon modified water-based acrylic polyurethane anticorrosive coating
CN112759999A
Temperature-resistant, acid-resistant and corrosion-resistant coating for brick desulfurization chimney and preparation method thereof
CN114058261A
Method for preparing biomass polyurethane based on high-activity lignin polyphenol and product
CN113861364A
Preparation method and application of cellulose nanocrystal modified waterborne polyurethane composite material
CN115894855A
Omniphobic polyurethane compositions, related articles, and related methods
US20210002410A1